2009
DOI: 10.1007/s11224-009-9423-2
|View full text |Cite
|
Sign up to set email alerts
|

Benzamidinium acetylsalicylate: crystal structure of the first salt with acetylsalicylate anion

Abstract: The first crystal structure of a non-coordinating acetylsalicylate anion containing salt was determined by X-ray crystallography. Benzamidinium acetylsalicylate crystallizes in the triclinic space group P " 1 (a = 9.8885 (5), b = 10.2769(5), c = 15.2656(7) Å , a = 87.219(4), b = 78.261(4) and c = 72.589(4) Z = 4, V = 1449.17(12) Å 3 , R1 = 0.0346 and wR2 = 0.0697). The structure comprises pairs of hydrogen bonded benzamidinium cations and acetylsalicylate anions connected into infinite chains through further N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In both polymorphic forms, the BenzamH + cations are not planar. The dihedral angles between the mean plane of the benzene ring and the amidinium group [20.2 (1) and 14.4 (1) for polymorph (I), and 23.6 (1) for polymorph (II)] are close to the values observed in benzamidine [22.7 (1) ; Barker et al, 1996] Kolev et al, 2009]. For both polymorphs this disposition is a consequence of an overcrowding effect, i.e.…”
Section: Commentsupporting
confidence: 53%
“…In both polymorphic forms, the BenzamH + cations are not planar. The dihedral angles between the mean plane of the benzene ring and the amidinium group [20.2 (1) and 14.4 (1) for polymorph (I), and 23.6 (1) for polymorph (II)] are close to the values observed in benzamidine [22.7 (1) ; Barker et al, 1996] Kolev et al, 2009]. For both polymorphs this disposition is a consequence of an overcrowding effect, i.e.…”
Section: Commentsupporting
confidence: 53%
“…For background to cyclobenzaprine, see: Commissiong et al (1981); Katz & Dube (1988); Cimolai (2009). For related structures, see: Bindya et al, (2007); Hemamalini & Fun (2010); Kolev et al (2009); Thanigaimani et al (2007). For graph-set notation, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…Cyclobenzaprine has been considered structurally related to the first-generation tricyclic antidepressants (Commissiong et al, 1981;Katz & Dube, 1988;Cimolai, 2009). The crystal structures of amitriptylinium picrate (Bindya et al, 2007), benzamidinium salicylate (Kolev et al, 2009), 2-amino-5-chloropyridinium salicylate (Hemamalini & Fun, 2010) and 2-amino-4,6-dimethoxypyrimidinium salicylate (Thanigaimani et al, 2007) have been reported. We now report the crystal structure of the title compound, C 20 H 22 N + .C 7 H 5 O 3 -.…”
Section: S1 Commentmentioning
confidence: 99%
“…From the probabilities of formation of 75 bimolecular ring motifs that have been determined (Allen et al, 1999), the rather poor performance of the amidinium-carboxylate heterodimer (P m = 0.51) can be explained by strong competition of alternative motifs. In contrast, in the case of salts containing the benzamidinium cation, although only a few structures have been reported, the R 2 2 (8) (Etter et al, 1990;Bernstein et al, 1995;Motherwell et al, 1999) one-dimensional heterosynthon with carboxylate or other oxygenate anions predominates (Kratochvíl et al, 1987;Portalone, 2008a;Kolev et al, 2009). These acid-base complexes are usually arranged in a dimeric motif, similar to that found in carboxylic acid dimers, via N + -HÁ Á ÁO À (AE)-charge-assisted hydrogen bonds (CAHB) (Gilli & Gilli, 2009), provided that ÁpK a [ÁpK a = pK a (base) À pK a (acid), where the pK a are for aqueous solutions] is sufficiently large.…”
Section: Commentmentioning
confidence: 99%